Analisis Permasalahan Belajar : Faktor-Faktor Efektivitas Proses Pembelajaran Pada Siswa - Erina Mifta Alvira; Arel Vaganza; Andromeda Putri; Bagus Setiawan (JURNAL PENDIDIKAN DAN ILMU SOSIAL (JUPENDIS), 2024)
Learning effectiveness refers to the extent of the process. Education or learning achieves the desired goals with good results. This can be measured through achievement of learning objectives, level of student understanding, improvement of skills, and use of knowledge gained in practical situations. Learning focus refers to the central point or main concern in the learning process. The learning process refers to a series of activities, interactions, and strategies used in an educational context to help students acquire knowledge, skills, understanding, and competencies. The effectiveness of learning is influenced by various factors that can influence it, the factors being competition and focus on learning.